Serum Starvation Enhances the Antitumor Activity of Natural Matrices: Insights into Bioactive Molecules from Dromedary Urine Extracts - Maria Noemi Sgobba; Biagia Musio; Carlos Iglesias Pastrana; Stefano Todisco; Nikola Schlosserovà; Federica Mastropirro; Maria Favia; Antonio Radesco; Iola F. Duarte; Anna De Grassi; Mariateresa Volpicella; Vito Gallo; et al. (Molecules)
Natural matrices have historically been a cornerstone in drug discovery, offering a rich source of structurally diverse and biologically active compounds. However, research on natural products often faces significant challenges due to the complexity of natural matrices, such as urine, and the limitations of bioactivity assessment assays. To ensure reliable insights, it is crucial to optimize experimental conditions to reveal the bioactive potential of samples, thereby improving the validity of statistical analyses. Approaches in metabolomics further strengthen this process by identifying and focusing on the most promising compounds within natural matrices, enhancing the precision of bioactive metabolite prioritization. In this study, we assessed the bioactivity of 17 dromedary urine samples on human renal cells under serum-reduced conditions (1%FBS) in order to minimize possible FBS-derived interfering factors. Using viability assays and Annexin V/PI staining, we found that the tumor renal cell lines Caki-1 and RCC-Shaw were more sensitive to the cytotoxic effects of the small molecules present in dromedary urine compared to non-tumor HK-2 cells. Employing NMR metabolomics analysis combined with detected in vitro activity, our statistical model highlights the presence of bioactive compounds in dromedary urine, such as azelaic acid and phenylacetyl glycine, underscoring its potential as a sustainable source of bioactive molecules within the framework of green chemistry and circular economy initiatives.